Overexpression of patatin-related phospholipase AIIIβ altered the content and composition of sphingolipids in Arabidopsis - Li, Maoyin; Markham, Jonathan E.; Wang, Xuemin (Frontiers in Plant Science, 2014)
In plants, fatty acids are primarily synthesized in plastids and then transported to the endoplasmic reticulum for synthesis of most of the complex membrane lipids, including glycerolipids and sphingolipids. The first step of sphingolipid synthesis, which uses a fatty acid and a serine as substrates, is critical for sphingolipid homeostasis; its disruption leads to an altered plant growth. Phospholipase As (PLAs) have been implicated in the trafficking of fatty acids from plastids to the endoplasmic reticulum. Previously, we found that overexpression of a patatin-related phospholipase, pPLAIIIβ, resulted in a smaller plant size and altered anisotropic cell expansion. Here, we determined the content and composition of sphingolipids in pPLAIIIβ-knockout and overexpression plants (pPLAIIIβ-KO and -OE). 3-keto-sphinganine, the product of the first step of sphingolipid synthesis, had a 26% decrease in leaves of pPLAIIIβ-KO while a 52% increase in pPLAIIIβ-OE compared to wild type (WT). The levels of free long-chain base species, dihydroxy-C18:0 and trihydroxy-18:0 (d18:0 and t18:0), were 38% and 97% higher, respectively, in pPLAIIIβ-OE than in WT. The level of complex sphingolipids ceramide d18:0-16:0 and t18:1-16:0 had a 2-fold increase in pPLAIIIβ-OE. The level of hydroxyceramide d18:0-h16:0 was 72% higher in pPLAIIIβ-OE compared to WT. The levels of several species of glucosylceramide and glycosylinositolphosphoceramide tended to be higher in pPLAIIIβ-OE than in WT. The total content of the complex sphingolipids showed a slightly higher in pPLAIIIβ-OE than in WT. These results revealed an involvement of phospholipase-mediated lipid homeostasis in plant growth.